2011
DOI: 10.1021/np200321s
|View full text |Cite
|
Sign up to set email alerts
|

p-Terphenyl and Diterpenoid Metabolites from Endophytic Aspergillus sp. YXf3

Abstract: Six new p-terphenyl derivatives, named 4″-deoxy-3-hydroxyterphenyllin (1), 4″-deoxy-5'-desmethyl-terphenyllin (2), 5'-desmethylterphenyllin (3), 4″-deoxycandidusin A (4), 4,5-dimethoxycandidusin A (5), and terphenolide (6), four new diterpenoids with norcleistanthane (aspergiloid A (12) and aspergiloid B (13)), cleistanthane (aspergiloid C (14)), and isopimarane (aspergiloid D (15)) type skeletons, and five known p-terphenyl compounds (7-11) were isolated from the fermentation broth of the plant endophytic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…[11] but in its p-quinol or leuco-form as occurs with corticin A described by Briggs et al [6]. This structure was confirmed by two-dimensional NMR experiments performed in the present work and also by comparison with other natural products described in the literature as candidusins [12]. The chemical shifts found for the methoxy groups and their comparison with 4''-deoxycandidusin A and 4,5dimethoxycandidusin A [12] confirmed that two of the three methoxy groups were the substituents at C-8 and C-8'.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…[11] but in its p-quinol or leuco-form as occurs with corticin A described by Briggs et al [6]. This structure was confirmed by two-dimensional NMR experiments performed in the present work and also by comparison with other natural products described in the literature as candidusins [12]. The chemical shifts found for the methoxy groups and their comparison with 4''-deoxycandidusin A and 4,5dimethoxycandidusin A [12] confirmed that two of the three methoxy groups were the substituents at C-8 and C-8'.…”
supporting
confidence: 89%
“…This structure was confirmed by two-dimensional NMR experiments performed in the present work and also by comparison with other natural products described in the literature as candidusins [12]. The chemical shifts found for the methoxy groups and their comparison with 4''-deoxycandidusin A and 4,5dimethoxycandidusin A [12] confirmed that two of the three methoxy groups were the substituents at C-8 and C-8'. The HMBC correlations between these methoxy groups at  4.34 and 4.31 ppm with the two quaternary aromatic carbon signals at  134.5 ppm agree with the same p-dimethoxybenzenic ring present in candidusin derivatives.…”
supporting
confidence: 87%
“…Compounds 83, 84, 85, and 88 exhibited moderate neuraminidase inhibitory activity and thus may work as antiviral agents. [67] Aspergillus tubingensis (GX1-5E), a mangrove endophyte, produced three dimeric naphtho-c-pyrones, named rubasperone A (95), rubasperone B (96), and rubasperone C (97). Moreover, two compounds, rubrofusarin (98) and rubrofusarin B (99), were also isolated.…”
Section: Endophyte-host Interactionmentioning
confidence: 99%
“…YXf3 from the leaf of Ginkgo biloba produced six p ‐terphenyl derivatives, 4″‐deoxy‐3‐hydroxyterphenyllin ( 80 ), 4″‐deoxy‐5′‐desmethylterphenyllin ( 81 ), 5′‐desmethylterphenyllin ( 82 ), 4″‐deoxycandidusin A ( 83 ), 4,5‐dimethoxycandidusin A ( 84 ), and terphenolide ( 85 ), five previously known p ‐terphenyl compounds ( 86 – 90 ), and four previously undescribed diterpenoids with norcleistanthane (aspergiloid A ( 91 ) and aspergiloid B ( 92 )), cleistanthane (aspergiloid C ( 93 )), and isopimarane (aspergiloid D ( 94 )) type skeletons. Compounds 83 , 84 , 85 , and 88 exhibited moderate neuraminidase inhibitory activity and thus may work as antiviral agents …”
Section: Introductionmentioning
confidence: 99%
“…Azaphilone compounds had a wide range of bioactivities including cytotoxic, antifungal, antimicrobial, antioxidant and antiinflammatory activities, [4][5][6][7][8] and could be generally produced by Penicillium, Chaetomium and Monascus. 3 In the course of our search for novel and/or bioactive metabolites from microbes lived in special niche, 4,9,10 five azaphilones including three new isochromophilones X-XII (1-3) and two known compounds sclerotioramine (4) 11 and isochromophilone VI (5) 12 were isolated from the solid-substrate fermentation cultures of an endophytic fungus Diaporthe sp. The structures were identified on the basis of extensive spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%